Nucleon Momentum Distributions and Elastic Electron Scattering form Factors for 22Ne, 26Mg and 30Si Nuclei - Flaiyh, Gaith Naima; Al-Rahmani, Altaf Abdul Majeed (Al-Nahrain Journal of Science, 2012)
The nucleon momentum distributions ( NMD) for the ground state and elastic electronscattering form factors have been calculated in the framework of the coherent fluctuation modeland expressed in terms of the weight function (fluctuation function). The weight function has beenrelated to the nucleon density distributions of nuclei and determined from theory and experiment.The nucleon density distributions( NDD) is derived from a simple method based on the use of thesingle particle wave functions of the harmonic oscillator potential and the occupation numbers ofthe states. The feature of long-tail behavior at high momentum region of the NMD has beenobtained using both the theoretical and experimental weight functions. The observed electronscattering form factors for Ne Mg 22 26 , and Si 30 nuclei are in reasonable agreement with the presentcalculations throughout all values of momentum transfer q.